Le pays normand. Paysages et peuplement (IXe-XIIIe siècles) - Mathieu Arnoux; Christophe Maneuvrier (Tabularia)
The devastation and depopulation of the Norman countryside taking place when Rollo settled in Rouen probably originate from a historiographic myth created by Dudo of Saint-Quentin to servethe history of the recent Norman dynasty. Everything, on the contrary, leads us to believe that rural structures were by no means deeply altered by the political changes of the 9th and 10th centuries. The presence of strong densities of population and the conservation of the urban network testify for example to a certain continuity of population, which does not rule out strong regional variations. It is also to this continuous population that one owes strange survivals in terms of administration and public tax system inherited from the Carolingian period, the homines liberi group having succeeded in defending itself against the gradual establishment of feudal institutions, as indicated by the famous episode of the great revolt of 996.